A dual-functional urea-linked conjugated porous polymer anchoring silver nanoparticles for highly efficient CO2 conversion under mild conditions. Issue 37 (14th September 2020) - Wang, Xiaoji; Li, Wang; Wang, Jianxin; Zhu, Jie; Li, Yuting; Liu, Xiaozhen; Wang, Liping; Li, Lin
Abstract : A dual-functional urea-based conjugated porous polymer (UCPP) linked by enol-imine anchoring silver nanoparticles for CO2 conversion. Abstract : A dual-functional urea-linked conjugated porous polymer (UCPP) assembled by enol–imine with ordered unit arrays that act as potential anchoring sites in the networks was fabricated, and was further applied as a support for Ag nanoparticles by the coordinate interaction between them. The UCPP not only can well confine the Ag particle size and facilitate high dispersion, but also can afford special CO2 -philic moieties to enhance the adsorption properties. The resulting Ag@UCPP as a heterogeneous catalyst exhibited excellent activity for the carboxylative cyclization of propargyl alcohols with CO2 under mild conditions, together with good recyclability, which is probably attributed to the synergistic effect of the UCPP on the adsorption and activation of CO2 and the immobilization of Ag nanoparticles. This work affords possible opportunities for the design and synthesis of a heterogeneous catalyst toward CO2 conversion.